Resilience moderates the relationship between emotional intelligence and clinical communication ability among Chinese practice nursing students: A structural equation model analysis. (November 2016) - Kong, Linghua; Liu, Yun; Li, Guopeng; Fang, Yueyan; Kang, Xiaofei; Li, Ping
Abstract: Objective: To examine the positive association between emotional intelligence and clinical communication ability among practice nursing students, and to determine whether resilience plays a moderating role in the relationship between emotional intelligence and clinical communication ability among Chinese practice nursing students. Methods: Three hundred and seventy-seven practice nursing students from three hospitals participated in this study. They completed questionnaires including the Emotional Intelligence Inventory (EII), Connor–Davidson Resilience Scale (CD-RISC-10), and Clinical Communication Ability Scale (CCAS). Structural equation modeling was used to analyze the relationships among emotional intelligence, resilience, and clinical communication ability. Results: Emotional intelligence was positively associated with clinical communication ability ( P  < 0.01). Resilience significantly affected clinical communication ability ( P  < 0.01) and moderated the relationship between emotional intelligence and clinical communication ability ( P  < 0.01). Conclusions: Emotional intelligence is positively related to clinical communication ability among Chinese practice nursing students, and resilience moderates the relationship between emotional intelligence and clinical communication ability, which may provide scientific evidence to aid in developing intervention strategies to improve clinical communication ability. Highlights: This study was the first to explore the relationship between EI, resilience, and clinical communication ability. This study verified the direct relationship between EI and clinical communication ability. Resilience could moderate the relationship between EI and clinical communication ability.